The client’s perspective regarding their welcoming at a rehabilitation clinic ENDEREÇO - Cruz, Sirlaine Vieira da; Ribeiro, Liliane Dias; Cabral, Lúcia Helena de Assis; Sampaio, Rosana Ferreira (Acta Fisiátrica, 2010)
The new healthcare measures proposed by the Brazilian National Humanization Policy stress the patients’ welcoming, which constantly seeks to recognize the needs of clients and the forms of satisfying these needs. Studies have demonstrated the importance of humanized care, in which listening to the client is a valuable tool for assessing the efficacy of the service of-fered to a particular population. The aim of the present study was to describe how clients per-ceive the manner in which they are received at a hand rehabilitation clinic and to analyze the most important factors. A qualitative approach was adopted, with semistructured interviews in which clients were asked about how they were received at the clinic in terms of access, posture, and technique. Content analysis consisted of arranging, classifying and analyzing the results. Twelve patients from a public hospital in the city of Belo Horizonte, Minas Gerais, Brazil, participated in the study. The patients considered good reception to be the most hu-manized manner of being received–– with care, politeness, and fondness. Communication between therapist and client proved to be important in building a trusting relationship, generating client satisfaction and favoring progress in the treatment. It was evident that a warm reception was a valuable therapeutic instrument for the rehabilitation professional. Having listening skills and revealing oneself to be sensitive to the needs of the client helps reduce the natural fear and anxiety experienced at the beginning of physical therapy treatment and facili-tates the entire process.